Patterns and predictors of cancer‐specific patient health portal usage among patients with cancer: results from the UWCCC Survivorship Program. (28th August 2021) - Luoh, Rebecca P.; Tevaarwerk, Amye J.; Chandereng, Thevaa; Smith, Elena M.; Carroll, Cibele B.; Emamekhoo, Hamid; Sesto, Mary E.
Abstract: Background: Portals can assist patients in managing their healthcare. Understanding how patients with cancer use portals can facilitate improvements in patient engagement in cancer care. This study sought to determine if patients with cancer used portals differently for cancer versus noncancer purposes. The effects of geographic residence (rural vs. urban residence) and cancer stage on portal usage were also investigated. Methods: We conducted a retrospective analysis of portal usage by patients seen at an NCI‐designated cancer center between 2015 and 2019. Demographics, cancer characteristics, and portal usage (number of successful logins, messages sent, and results viewed) were extracted. Messages sent and results viewed in the portal were deemed oncologist‐specific and cancer specific if sent to or ordered in medical oncology departments, respectively. Results: The analysis included a total of 5950 patients with cancer. Patients were less likely to send and view oncologist‐specific messages compared to non‐oncologist‐specific messages. They were also less likely to view cancer results compared to noncancer results. Compared to urban counterparts, patients residing in rural areas had lower odds of having any logins and logged in less frequently during the year of diagnosis. Compared to patients with non‐metastatic disease, individuals with metastatic disease were more likely to become frequent portal users. Conclusions: Patients may use portals differently for cancer versus noncancer purposes; urban residence and metastatic cancer were associated with more frequent usage. Further investigation can inform interventions to increase accessibility for groups at a disadvantage related to the use of this technology and to help patients better leverage portals to manage their cancer. Abstract : Healthcare systems have come to increasingly rely on patient health portals to engage patients; however, patients with cancer may use portals for cancer purposes differently than for noncancer purposes. Our analysis of nearly 6000 patients with cancer suggests that there is a difference in cancer versus noncancer use and that factors such as age, rural residence, and non‐metastatic stage make patients less likely to access portals.